Idiopathic Adulthood Ductopenia: ‘It Is Out There’ - Bilal, Mohammad (Case Rep Gastroenterol, 2016)
Idiopathic adulthood ductopenia (IAD) is a chronic cholestatic entity of unknown origin characterized by loss of inter-lobular bile ducts that was first described two decades ago. Although the diagnostic criteria have been described in detail, IAD continues to be a rare diagnosis. Our thorough literature search revealed less than a hundred cases of IAD reported. Here we present a 34-year-old female with no significant past history who was evaluated for persistent elevation of serum alkaline phosphate levels. Serology was negative for all viral hepatitides, and a chronic liver disease workup was unremarkable. Magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography did not reveal any abnormalities in the biliary tree. Finally, a liver biopsy demonstrated ductopenia involving greater than 50% of the portal triads, making a diagnosis of IAD. Since the disease can progress rapidly, close follow-up is warranted, so liver transplantation can be pursued if deemed necessary.